2015
DOI: 10.3389/fpls.2015.01176
|View full text |Cite
|
Sign up to set email alerts
|

A Bird’s-Eye View of Molecular Changes in Plant Gravitropism Using Omics Techniques

Abstract: During evolution, plants have developed mechanisms to adapt to a variety of environmental stresses, including drought, high salinity, changes in carbon dioxide levels and pathogens. Central signaling hubs and pathways that are regulated in response to these stimuli have been identified. In contrast to these well studied environmental stimuli, changes in transcript, protein and metabolite levels in response to a gravitational stimulus are less well understood. Amyloplasts, localized in statocytes of the root ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 146 publications
0
18
0
Order By: Relevance
“…Plants in spaceflight differentially express genes compared to their ground controls, suggesting that physiological adaptation is taking place in plants on orbit. There have now been a number of transcriptomic and proteomic comparisons of Arabidopsis and other plants grown in spaceflight environments [ 19 , 23 , 38 , 46 – 57 ] and the topic of plant growth in space has been recently reviewed [ 58 63 ]. In addition, there is more to growing in an orbital environment than the simple removal of gravity.…”
Section: Discussionmentioning
confidence: 99%
“…Plants in spaceflight differentially express genes compared to their ground controls, suggesting that physiological adaptation is taking place in plants on orbit. There have now been a number of transcriptomic and proteomic comparisons of Arabidopsis and other plants grown in spaceflight environments [ 19 , 23 , 38 , 46 – 57 ] and the topic of plant growth in space has been recently reviewed [ 58 63 ]. In addition, there is more to growing in an orbital environment than the simple removal of gravity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, it has been suggested that altered ROS signalling in response to the spaceflight environment could affect plant growth and development indirectly via changes in hormonal influx within the plants (Schüler et al 2015). OMG1 was found to regulate the expression of ROS-associated genes GRX480 and MYB77 .…”
Section: Discussionmentioning
confidence: 99%
“…The physiological impact of spaceflight is reflected in the patterns of gene expression. Irrespective of plant growth hardware, duration in space or age of plants, one consensus is that spaceflight elicits responses from pathways associated with cell wall remodelling, cell polarity, phytohormone-mediated processes, as well as general stress responses, such as wounding, pathogen defence, heat shock and reactive oxygen species (ROS) (Joo et al 2001; Paul et al 2005, 2012b, 2013a; Correll et al 2013; Zupanska et al 2013; Ferl et al 2014; Mazars et al 2014; Sugimoto et al 2014; Zhang et al 2014; Kwon et al 2015; Schüler et al 2015). In addition, a large proportion of genes differentially expressed in spaceflight encode unknown proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies in Arabidopsis have identified several genes involved in shoot gravitropism such as SGR genes and PHOSPHOGLUCOMUTASE genes (Hashiguchi et al, 2013(Hashiguchi et al, , 2014Kim et al, 2016;Kolesnikov et al, 2016). Although other studies have used "omics" techniques and identified gravitropism-related genes or proteins in several species (Moseyko et al, 2002;Kimbrough et al, 2004;Hu et al, 2013Hu et al, , 2015Schenck et al, 2013;Taniguchi et al, 2014;Gerttula et al, 2015;Schüler et al, 2015), the direct link between tiller or branch angle and gravitropism has not yet been established.…”
Section: Introductionmentioning
confidence: 99%